Autophagy is a pro-survival adaptive response to heat shock in bovine cumulus-oocyte complexes - Latorraca, Lais B. [UNESP]; Feitosa, Weber B.; Mariano, Camila; Moura, Marcelo T.; Fontes, Patrícia K. [UNESP]; Nogueira, Marcelo F. G. [UNESP]; Paula-Lopes, Fabíola F. [UNESP] (Springer Nature, 2020)
Autophagy is a physiological mechanism that can be activated under stress conditions. However, the role of autophagy during oocyte maturation has been poorly investigated. Therefore, this study characterized the role of autophagy on developmental competence and gene expression of bovine oocytes exposed to heat shock (HS). Cumulus-oocyte-complexes (COCs) were matured at Control (38.5 °C) and HS (41 °C) temperatures in the presence of 0 and 10 mM 3-methyladenine (3MA; autophagy inhibitor). Western blotting analysis revealed that HS increased autophagy marker LC3-II/LC3-I ratio in oocytes. However, there was no effect of temperature for oocytes matured with 3MA. On cumulus cells, 3MA reduced LC3-II/LC3-I ratio regardless of temperature. Inhibition of autophagy during IVM of heat-shocked oocytes (3MA-41 °C) reduced cleavage and blastocyst rates compared to standard in vitro matured heat-shocked oocytes (IVM-41 °C). Therefore, the magnitude of HS detrimental effects was greater in the presence of autophagy inhibitor. Oocyte maturation under 3MA-41 °C reduced mRNA abundance for genes related to energy metabolism (MTIF3), heat shock response (HSF1), and oocyte maturation (HAS2 and GREM1). In conclusion, autophagy is a stress response induced on heat shocked oocytes. Inhibition of autophagy modulated key functional processes rendering the oocyte more susceptible to the deleterious effects of heat shock.